Analisis Yuridis Perkembangan Perbankan Syariah di Indonesia dan Malaysia : (Studi Perbandingan Hukum) - Raka Haikal Anfasya; Handar Subhandi Bakhtiar; Atik Winanti (STIKes Ibnu Sina Ajibarang, 2025)
This research analyzes the legal development of Islamic banking in Indonesia and Malaysia through a comparative law approach. Islamic banking has become an important component of the global financial system, yet its growth varies across countries. Indonesia's Islamic banking industry, while experiencing significant progress in recent years, still faces regulatory and institutional challenges. In contrast, Malaysia has emerged as a global hub for Islamic finance due to its integrated regulatory framework, strong government support, centralized Shariah compliance system, and established human resource development. This study employs normative legal research using primary and secondary legal sources, and applies comparative legal theory. The findings highlight the importance of legal harmonization, centralization of fatwa authorities, active government involvement, and comprehensive infrastructure development in supporting the growth of Islamic banking. Lessons from Malaysia's experience can serve as valuable references for Indonesia to enhance its Islamic banking industry and improve its competitiveness in the global market.